The Relationship between Cupping Therapy and Herbs on Stress Levels in Hypertensive Patients at Griya Sehat Bogor Islami Johar Baru Bogor city - Hernida Dwi Lestari; Didi Sutisna; Al-Bahra (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2022)
The purpose of this study was to determine the relationship between cupping and herbal therapy on stress levels in hypertensive patients at Griya Sehat Bogor Islami Johar bru, Bogor City. In this study, the authors used a quantitative descriptive design with a Cross Sectional approach. The researcher used a cross sectional approach. The population in this study were hypertensive patients with anxiety who were treated at Griya Sehat Bogor Islami Johar Baru, Bogor City, taken from the average monthly patient in the last 4 months. The sampling technique used in this study is incidental sampling. The sample taken in this study is purposive sampling, which is a sampling technique that is included in non-probability sampling. The distribution of respondents by gender showed that there were 3 patients with hypertension who experienced stress (20%) and 12 women or (80%). The distribution of respondents by age shows that the most age is 35-45 years as many as 9 people or (60%) and the smallest age is 45-65 years. The distribution of respondents according to education shows that the most junior high school education is 6 people or (40%) and the lowest is PT as much as 1 person or (6.7%). The distribution of respondents by occupation shows that the most education is self-employed and laborers respectively as many as 7 people or (46.7%) and the lowest is civil servants as much as 1 person or (6.7%). There is an effect of cupping and herbal therapy at the Johar Islamic Herbal Healthy House in Bogor City on the level of stress with a significance of p value = 0.001 < = 0.05.